Epidemiology of Haemorrhagic Septicaemia in Cattle and Buffaloes in Peninsular Malaysia - Singh, Bisht Khadak (2006)
A retrospective study on haemorrhagic septicaemia (HS) was conducted through a questionnaire survey in 64 districts of Peninsular Malaysia. One thousand four hundred and eighty nine deaths (1489) due to HS were reported from January 1993 to December 2003. Outbreaks of the disease were reported almost every year despite many precautionary measures taken. Out of the eleven (1 1) states surveyed in Peninsular Malaysia, HS was identified as endemic in Terengganu, Kelantan and Perak while the remaining states were considered as no disease. Time series seasonal decomposition method distinguished the patterns (seasonal, secular trend, cyclic and irregularity fluctuations) of the HS occurrence and its relationship with the climatological pattern (rainfall, temperature and humidity), while movement of animals during the main festive seasons and vaccination was also described. Two hundred and four buffaloes (204) and four (4) cattle died of HS in Batang Padang, Perak in 2003. An epidemiological investigation was performed during the outbreak where clinical samples were collected, farmers were interviewed and field visit was made. Pasteurella multocida B:2 was isolated and identified from both the heart blood and nasal swabs of the affected animals. The buffaloes that died in the pond in the grazing area played a major role in the rapid spread of the disease. The explosive outbreak was due to a combination of factors such as introduction of the healthy carriers fiom the endemic areas, significant climatic changes and low immune status of the susceptible herds. Development of an ELISA test system for HS diagnosis was validated based on samples from both HS infected and uninfected populations. An area under receiver operating characteristic (ROC) curve showed that the test was highly accurate, separating the population into two different disease status groups. The cut-off value obtained by the ROC analysis for indirect ELISA gave 86.4% diagnostic sensitivity and 84.2% diagnostic specificity, based on 0.5 1 OD cut-off point. The status of cattle as carriers of P. multocida B:2 was investigated in three bovine herds in the no disease areas and three bovine herds in the endemic areas. A total of 186 animals from the selected farms were selected and followed for three to five consecutive times over a period of six months to determine their status as carriers of the HS-causing organism. Isolation of the organism was performed using mice and the serum antibody was detected using indirect ELISA. Bacteriological analysis did not reveal any of the sampled animals to harbour the HS-causing organism at any point during the 6-month study period. However, some level of immunity appeared to be existed within these populations. The mean optical density (OD) values in the no disease areas were lower than the mean OD values in the endemic areas (pC.05).ELISA revealed an increase in the antibody titers after the 2"d months of study in the endemic areas. However, this could be the result of vaccination. The role of carrier animals remained unclear and poorly understood. It could be postulated that latent carriers (if they exist within these populations) remain without shedding for a period of 6 months. The limitations during the field investigation included poor cooperation from the farmers, poor understanding by farmers on the importance of herd health program and the archaic animal management and husbandry. Pasteurella multocida B:2 isolated fiom the outbreak investigations were further studied by species specific and type specific multiplex PCR method. The REP-PCR and single primer PCR provided a better trace method for the epidemiological investigation in the disease outbeaks giving many strains that caused the HS. The - -- - - results of the plasmid profile showed identical patterns in all isolates.ELISA revealed an increase in the antibody titers after the 2"d months of study in the endemic areas. However, this could be the result of vaccination. The role of carrier animals remained unclear and poorly understood. It could be postulated that latent carriers (if they exist within these populations) remain without shedding for a period of 6 months. The limitations during the field investigation included poor cooperation from the farmers, poor understanding by farmers on the importance of herd health program and the archaic animal management and husbandry. Pasteurella multocida B:2 isolated fiom the outbreak investigations were further studied by species specific and type specific multiplex PCR method. The REP-PCR and single primer PCR provided a better trace method for the epidemiological investigation in the disease outbeaks giving many strains that caused the HS. The - -- - - results of the plasmid profile showed identical patterns in all isolates.vELISA revealed an increase in the antibody titers after the 2"d months of study in the endemic areas. However, this could be the result of vaccination. The role of carrier animals remained unclear and poorly understood. It could be postulated that latent carriers (if they exist within these populations) remain without shedding for a period of 6 months. The limitations during the field investigation included poor cooperation from the farmers, poor understanding by farmers on the importance of herd health program and the archaic animal management and husbandry. Pasteurella multocida B:2 isolated fiom the outbreak investigations were further studied by species specific and type specific multiplex PCR method. The REP-PCR and single primer PCR provided a better trace method for the epidemiological investigation in the disease outbeaks giving many strains that caused the HS. The - -- - - results of the plasmid profile showed identical patterns in all isolates